2023
DOI: 10.1167/jov.23.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Quick, eyes! Isolated upper face regions but not artificial features elicit rapid saccades

Abstract: Human faces elicit faster saccades than objects or animals, resonating with the great importance of faces for our species. The underlying mechanisms are largely unclear. Here, we test two hypotheses based on previous findings. First, ultra-rapid saccades toward faces may not depend on the presence of the whole face, but the upper face region containing the eye region. Second, ultra-rapid saccades toward faces (and possibly face parts) may emerge from our extensive experience with this stimulus and thus extend … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Especially the eye region has been suggested to play a role in rapid face detection. Most saccades land near the eyes (Kauffmann et al, 2021) and upper face regions elicit faster saccadic reaction times than lower and even whole faces (Broda et al, 2023). This is in line with recordings from face-selective cells in macaques showing that faces only containing an eye elicit rapid neural responses (Issa & DiCarlo, 2012).…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Especially the eye region has been suggested to play a role in rapid face detection. Most saccades land near the eyes (Kauffmann et al, 2021) and upper face regions elicit faster saccadic reaction times than lower and even whole faces (Broda et al, 2023). This is in line with recordings from face-selective cells in macaques showing that faces only containing an eye elicit rapid neural responses (Issa & DiCarlo, 2012).…”
Section: Introductionsupporting
confidence: 82%
“…Faces elicit faster and more accurate saccades than other types of objects (Crouzet et al, 2010), which may hinge on the eye region (Broda et al, 2023;Kauffmann et al, 2021). However, it is still unclear whether rapid saccades are face-specific, and if individual differences in the tendency to immediately fixate faces during free-viewing are related to reaction time advantage for faces in the Saccadic Choice Task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, amygdala HGBA encodes information about facial features such as the eyes (Guex et al, 2023). As eye movements are usually most prominent after 200 ms during face processing (Broda et al, 2023;Spiering & Dimigen, 2023)-which is slower than the effect onset in amygdala HGBA in the present study-amygdala HGBA might predispose gaze shifts toward relevant facial features rather than reflect them. The findings reported by Jha et al (2023) support this view: They demonstrated a predictive value of amygdala HGBA for saccades in response to faces.…”
Section: A Neutral Focus Enhances the Detection Of Emotion In The Amy...mentioning
confidence: 53%